A SURVEY ON THE MAJOR AND TRACE ELEMENT LEVELS IN HONEYS PRODUCED AND CONSUMED IN ELAZIG, TURKEY - Aygun, Osman (Parlar Scientific Publications (P S P), 2020)
The aim of this study was to determine the concentrations of major and trace elements in honeys produced and consumed in Elazig province of Turkey. The major (Na, K, Ca, Mg, P) and trace (Fe, Cu, Zn, Mn, Se, Cr, V) element levels of 30 natural liquid honey samples were determined by inductively coupled plasma with mass spectrophotometer (ICP-MS). The mean concentrations of the major and trace elements in honey samples decreased in the following order: K > Na > P > Mg > Ca > Fe > Zn > Mn > Cu > Cr > V > Se, with values of 230.20, 84.90, 39.15, 13.18, 9.16, 1.42, 1.36, 0.14, 0.12 mg/kg and 5.74, 2.41, 2.21 mu g/kg, respectively. The results indicated that the honeys produced and consumed in Elazig were safe and of good quality for human consumption with regard to the concentrations of major and trace elements.
Keywords: Honey; mineral; trace element; ICP-MS; Elazig